Studi Literatur Terminologi Media Dan Teknologi Pembelajaran (Sejarah Dan Perbedaan Istilah) - Rais , Muhammad; Muhammad Yaumi; Yusuf T, Muh (Indonesian Journal Publisher, 2024)
This research aims to examine in depth the terminology and basic differences between learning media and learning technology as well as strategies for combining media and learning technology which includes definitions, characteristics and practical application of both concepts in the educational environment. This research is library research, namely the act of utilizing library resources, both print and online, to search for media terminology and learning technology both conceptually and in its implementation in learning. Researchers scoured national and university libraries, several web-based search engines to collect relevant digital information. The research results show that the term learning media is a tool used to convey information in the learning process, while learning technology is a system used to design, manage and evaluate the learning process. Both have an important role in improving the quality of education).